Preparation and application of polyaluminium silicate chloride in coagulation process - Selvan, Murugan (2010)
Coagulation is one of the most important method in chemical treatment of water and wastewater. There are several types of coagulant used in water and wastewater treatment. Most of the inorganic and some polymer coagulants are still not very effective on removing suspended solid and give side effects. A lot of research were done by scientist around the world in coagulation and flocculation field to improve the properties of prepolymerized coagulants, such as polyaluminium chloride (PAC). Recently, Bao-Yu Gao et al.reported that under certain conditions polyaluminum silicate chloride (PASiC), a new type of inorganic polymer coagulant,having a larger particle size and better turbidity removal efficiency than PAC. Coagulation test were done for both water and wastewater PASiC and the results were compared with conventional coagulants (Alum and PAC). For water treatment, PASiC removed 99.45% of turbidity, 68.75% of COD and 48.31% of BOD at optimum coagulant dosage. And for wastewater, it removed 90.14% of turbidity, 89.72% of COD and 46.7%BOD. From this research we can conclude that polyaluminium silicate chloride is very effective in removing suspended solids in both water and wastewater and very good in every aspect compare to other two conventional coagulant, Alum and PAC.